Monocyte chemoattractant protein-1 affects migration of hippocampal neural progenitors following status epilepticus in rats - Hung, Yu-Wen (BioMed Central, 2013)
BACKGROUND: Epilepsy is a common brain disorder characterized by a chronic predisposition to generate spontaneous seizures. The mechanisms for epilepsy formation remain unknown. A growing body of evidence suggests the involvement of inflammatory processes in epileptogenesis. In the present study, we investigated the involvement of monocyte chemoattractant protein-1 (MCP-1) in aberrant migration of hippocampal progenitors in rats after the insult of status epilepticus (SE). METHODS: SE was induced with pilocarpine in Sprague–Dawley rats. Transcriptional expression of MCP-1 in the dentate gyrus (DG) was measured using quantitative real-time PCR. From 1 to 28 days after SE, the temporal profiles of MCP-1 protein expression in DG were evaluated using enzyme-linked immunosorbent assay. Chemokine (C-C motif) receptor 2 (CCR2) expression in doublecortin-positive neuronal progenitors was examined using double-labeling immunohistochemistry. The involvement of MCP-1/CCR2 signaling in aberrant neuronal progenitor migration in the epileptic hippocampus was assessed in the SE rats using a CCR2 antagonist, RS102895, and the ectopic migration of neuronal progenitors was determined using Prox1/doublecortin double immunostaining. RESULTS: After SE, MCP-1 gene was significantly upregulated and its corresponding protein expression in the DG was significantly increased on days 1 and 3. Some hilar ectopic progenitor cells of SE rats expressed the MCP-1 receptor, CCR2. Notably, the ectopic migration of neuronal progenitors into hilus was attenuated by a blockade of the MCP-1/CCR2 interaction with a selective CCR2 inhibitor, RS102895. CONCLUSIONS: An increase in dentate MCP-1 is associated with seizure-induced aberrant migration of neuronal progenitors through the interaction with CCR2. The upregulation of MCP-1 after an insult of SE may play a role in the generation of epilepsy.